2022
DOI: 10.3390/foods11071044
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and Diet Supplements in Crohn’s Disease: A General Overview of the Most Promising Approaches in the Clinic

Abstract: Crohn’s disease (CD) is a chronic inflammatory gastrointestinal disorder requiring lifelong medications. The currently approved drugs for CD are associated with relevant side effects and several studies suggest an increased use of nutraceuticals among CD patients, seeking for what is perceived as a more “natural” approach in controlling this highly morbid condition. Nutraceuticals are foods or foods’ components with beneficial health properties that could aid in CD treatment for their anti-inflammatory, analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“… Compare et al, 2017 reported L. casei DG lower pro-inflammatory IL-6, IL-8, TLR-4 and IL-1a and increase IL-10 cytokinelevels in the colonic mucosa of post-infectious IBD subjects. Additionally, L. casei and L. bulgaricus significantly lowered the pro-inflammatory cytokine TNF-α in colonic mucosal samples from CD patients ( De Conno et al, 2022 ). The Treg cells are another immunological player involved in immune-modulation and tolerance.…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
“… Compare et al, 2017 reported L. casei DG lower pro-inflammatory IL-6, IL-8, TLR-4 and IL-1a and increase IL-10 cytokinelevels in the colonic mucosa of post-infectious IBD subjects. Additionally, L. casei and L. bulgaricus significantly lowered the pro-inflammatory cytokine TNF-α in colonic mucosal samples from CD patients ( De Conno et al, 2022 ). The Treg cells are another immunological player involved in immune-modulation and tolerance.…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
“…Thus, it is not surprising that over the last decades, alternative strategies based on the use of pre-/probiotics, have been developed to complement or even replace pharmacological therapy for the treatment of IBD [ 112 ]. The role of prebiotics and probiotics in CD management has been extensively discussed and reviewed in detail elsewhere [ 113 , 114 , 115 , 116 , 117 ]. Several probiotic strains known to have beneficial effects on health have been tested in human clinical studies including Bifidobacterium spp., Lactobacillus spp., E. coli Nissle 1917, and Saccharomyces boulardii [ 19 ].…”
Section: Nutritional Strategies In CD Treatment and Managementmentioning
confidence: 99%
“…Noteworthy, while the efficacy of probiotics such as VSL#3, containing a mixture of eight bacterial strains including four Lactobacillus spp., three strains of Bifidobacterium spp., and Streptococcus salivarius subsp. Thermophilus, has been well established for UC management, but attempts to prove their usefulness in CD have produced controversial results [ 113 ]. These incongruences might be in part explained by differences in study design, methodology, the variety of pre- or probiotics used, and/or patients’ compliance.…”
Section: Nutritional Strategies In CD Treatment and Managementmentioning
confidence: 99%
“…Several studies have shown that, although sometimes using probiotics could not be helpful and effective in treating Crohn's disease (CD), as a subtype of IBD (De Conno et al . 2022), various probiotic strains, including Bifidobacterium spp, play a beneficial role in controlling IBD through enhancement of epithelial barrier function, causing homeostasis and modulation of the immune system (Magrone and Jirillo 2013; Moratalla et al . 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Taking probiotics could be a beneficial way to control inflammation, irritable bowel syndrome (IBS) and IBD (Moayyedi et al 2019). Several studies have shown that, although sometimes using probiotics could not be helpful and effective in treating Crohn's disease (CD), as a subtype of IBD (De Conno et al 2022), various probiotic strains, including Bifidobacterium spp, play a beneficial role in controlling IBD through enhancement of epithelial barrier function, causing homeostasis and modulation of the immune system (Magrone and Jirillo 2013;Moratalla et al 2016). Studies explained that Bifidobacterium longum 536 (BB536), for example, can induce remission in patients with ulcerative colitis (UC), a subtype of IBD (Matsuoka et al 2018).…”
Section: Introductionmentioning
confidence: 99%